Joined at the heart the transformation of the American family - Gore, Al 1948- (Audio Renaissance, 2002)
Former President Al Gore and his wife, family advocate Tipper Gore, consider family their bedrock. Now, in this provocative and personal book, they explore the myriad ways in which the family is being redefined. New economic pressures, cultural changes, and demographic shifts have fundamentally altered the way we live our lives. But if American families can no longer rely on many traditional landmarks, they are finding creative new ways to define, enrich,and honor their commitment to this most essential of all relationships. As they explore the changing nature of the family, the Gores introduce us to a variety of families they have come to know over the years. They share personal stories, explore issues such as communication, money, play, and resilience, and provide invaluable insights into ways families are responding to challenges.